Imagens da guerra: Brasil, Palestina e Portugal - Maranhão, Cristina (2013)
This thesis seeks to comprehend the imagetic construction of contemporary wars transmitted by national and international media, through the case study of two current conflicts: the war between police and drug dealers at Rio de Janeiro´s favelas of Complexo do Alemão, and the armed conflict between israelis and palestinians in the Gaza Strip, involving the Palestine Question. Devided in two parts, war and image, this work shows how significative changes occurred in the form of the warfare, associated to new global economic formula, originated from globalization and mundialization. These changes reflected in the form of representing the armed conflicts and therefore in the current photojournalism. . From the observation of significative diferences in the field of images, we focus in two aspects: the image as an action of imagination, and the image as excessive production of clichés from the society of the spectacle . This thesis proposes the construction of a western imagery catalog, elaborated from the relationship between the analysed images of conflicts and the images collected from paints, engraving or photographs. This proposition occured because we realised that there is an imagetic construction of war, wich is responsable for the imaginary of the warrior and of conflicts. Images of war today have changed along with changes of the armed conflict universe, demonstrating a reverberation of images and specific subjects turned into simple pictural clichés, wich in many cases do not represent the violence experienced by the population envolved. This reverberation expresses the generalization of images of war today